International students' experiences of integrating into the workforce. Issue 1 (4th March 2013) - Nunes, Sarah; Arthur, Nancy
<x xml:space="preserve">Abstract</x> This study explored the integration experiences of 16 international students entering the Canadian workforce using a semistructured interview and constant comparison method. The international students were pursuing immigration to Canada, despite unmet job prospects. Students recommended that employers refrain from discriminating against students because of their international status and recognize the value of a diverse labor force. Students recommended that career services personnel help students build networks and employment contacts through pregraduation work experience. Incoming international students were advised to educate themselves about cultural norms for social and work interactions, research potential job opportunities, and create a professional network prior to degree completion.